Capacitive Ammonia Sensor Based on Graphene Oxide/Polyaniline Nanocomposites. Issue 7 (16th December 2021) - Wu, Chenggen; Han, Lei; Zhang, Jichao; Wang, Yongqing; Wang, Rui; Chen, LiJun
Abstract: Toxic and irritant gases such as ammonia in enclosure space could destroy the respiratory system with an unobtrusive way. Monitoring high‐risk gases are imperative when humans expose in a vulnerable environment with unpredictable gases. Capacitive sensors are supposed to be an ideal choice applying to contactless gas sensing in enclosed space. This research develops an innovative model based on barrier capacitance theory for capacitive ammonia sensor. A capacitive ammonia sensor based on graphene oxide/polyaniline (GO/PANI) nanocomposites, which can be attached to enclosure space (pipes, storage tanks, etc.), is manufactured and exhibits high sensitivity (49.3 × 10 –5 ppm) and fast response (≈200 s) in the ammonia concentration range of 0–100 ppm. In particular, GO/PANI nanocomposites are modeled as barrier capacitance. The model of ammonia sensor is described as width variation of space charge region in GO/PANI barrier capacitance which is caused by electron injection from adsorbed ammonia molecule. Variation trend of the model is consistent with the experimental results. Maximum deviation is limited to 9.25% in ammonia concentration range of 0–100 ppm between theoretical and experimental results. The model is able to accomplish the accurate quantitative analysis for capacitive ammonia sensors and provides an exhilarating enlightenment for other capacitive gas sensors. Abstract : This research develops an innovative model based on barrier capacitance theory for capacitive ammonia sensor with graphene oxide/polyaniline nanocomposites. The model is described as width variation of space charge region caused by electron injection from adsorbed ammonia molecule. Maximum deviation is limited to 9.25% in the range of 0–100 ppm ammonia between theoretical and experimental results.